Urban Wetlands: A Review on Ecological and Cultural Values - Somayeh Alikhani (MDPI AG, 2021)
Wetlands are a critical part of natural environments that offer a wide range of ecosystem services. In urban areas, wetlands contribute to the livability of cities through improving the water quality, carbon sequestration, providing habitats for wildlife species, reducing the effects of urban heat islands, and creating recreation opportunities. However, maintaining wetlands in urban areas faces many challenges, such as the reduction of hydrological functions, changed water regimes due to barriers, contamination by wastewater, habitat loss due to land-use change, and loss of biodiversity due to the entry of alien species. In this article, we review the theoretical background of wetlands in urban areas through the existing studies in the literature. We provide knowledge on urban wetlands and highlight the benefits of these wetlands in urban areas. These benefits include sustainability, biodiversity, urban heat islands, social perception, and recreation values. We also summarize the objectives, methodologies, and findings of the reviewed articles in five tables. In addition, we summarize the critical research gaps addressed in the reviewed articles. Our review study addresses the research gaps by performing a rigorous analysis to identify significant open research challenges, showing the path toward future research in the field. We further discuss and highlight the role of policymakers and stakeholders in preserving wetlands and finally present our conclusions.